2022
DOI: 10.3390/polym14122442
|View full text |Cite
|
Sign up to set email alerts
|

Active Flexible Films for Food Packaging: A Review

Abstract: Active food packaging is a dynamic area where the scientific community and industry have been trying to find new strategies to produce innovative packaging that is economically viable and compatible with conventional production processes. The materials used to develop active packaging can be organized into scavenging and emitting materials, and based on organic and inorganic materials. However, the incorporation of these materials in polymer-based flexible packaging is not always straightforward. The challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 88 publications
0
19
0
2
Order By: Relevance
“…Since this technology omits the stage of adding anything directly into the food, it is convenient and satisfactory from both the manufacturer’s and consumer’s perspectives. Active packaging films have been employed successfully in the packaging of food products such as meat and fish products, dairy products, vegetables, bread and bakery products, etc., [ 47 ].…”
Section: Fundamentals Of Active Packagingmentioning
confidence: 99%
“…Since this technology omits the stage of adding anything directly into the food, it is convenient and satisfactory from both the manufacturer’s and consumer’s perspectives. Active packaging films have been employed successfully in the packaging of food products such as meat and fish products, dairy products, vegetables, bread and bakery products, etc., [ 47 ].…”
Section: Fundamentals Of Active Packagingmentioning
confidence: 99%
“…In recent years, extensive research on active food packaging has aimed to provide new materials to maintain microbial food integrity beyond traditional packaging systems ( Norrrahim et al, 2021 ). However, many active food packaging strategies are still in their infancy, demand complex functionalization and therefore can only address single steps in the food supply chain ( Azevedo et al, 2022 ). In contrast, the sources of microbial contaminants are manifold and may occur in all steps of food production, transportation, storage and preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Several literature studies have reported the fabrication of antimicrobial and antibacterial polymer films. 3,4 In this area, Zeolite-supported silver-based technologies as antimicrobial agents are widely recognized. 5,6 These technologies have gained significant attention due to their effectiveness in controlling microbial growth and their potential application in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Several literature studies have reported the fabrication of antimicrobial and antibacterial polymer films 3,4 . In this area, Zeolite‐supported silver‐based technologies as antimicrobial agents are widely recognized 5,6 .…”
Section: Introductionmentioning
confidence: 99%